2021
DOI: 10.1097/mpg.0000000000003155
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents With Inflammatory Bowel Disease Have Decreased Rates of Health Maintenance Visits

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In our sample, this finding could not be replicated. Comparable studies looking at factors influencing health service utilisation in PIBD are limited and focused on the USA, making comparisons to a German population difficult [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, this finding could not be replicated. Comparable studies looking at factors influencing health service utilisation in PIBD are limited and focused on the USA, making comparisons to a German population difficult [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in the incidence and prevalence of PIBD in recent years, especially in developed countries [ 7 9 ], and the description of a gap between guidelines and real-world medicine [ 10 12 ] research on healthcare provision for this patient group has gained traction [ 13 15 ]. In German speaking countries, the implementation of multidisciplinary care teams for the treatment of PIBD is mostly coordinated by the GPGE e.V.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that AYA with public insurance, a mental health history, medication nonadherence, and evidence of active disease may be at greater risk for suboptimal and poor health outcomes at transition. Moran et al (5) examined health maintenance visits (HME) with primary care provider in patients with IBD compared to controls. Overall, patients with IBD had less frequent HME (62% vs 74%, P ¼ 0.0486).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…To the Editor: We read with interest the recent study by Moran et al (1). They found that adolescents with inflammatory bowel disease (iBD) have lower rates of health maintenance visits with their primary care physicians (PCPs), and lower rates of certain vaccinations, compared with their peers.…”
mentioning
confidence: 99%